2017
DOI: 10.1093/eurheartj/ehx008
|View full text |Cite
|
Sign up to set email alerts
|

Performance of hospitals according to the ESC ACCA quality indicators and 30-day mortality for acute myocardial infarction: national cohort study using the United Kingdom Myocardial Ischaemia National Audit Project (MINAP) register

Abstract: AimsTo investigate the application of the European Society of Cardiology Acute Cardiovascular Care Association quality indicators (QI) for acute myocardial infarction for the study of hospital performance and 30-day mortality.Methods and resultsNational cohort study (n = 118,075 patients, n = 211 hospitals, MINAP registry), 2012-13. Overall, 16 of the 20 QIs could be calculated. Eleven QIs had a significant inverse association with GRACE risk adjusted 30-day mortality (all P < 0.005). The association with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 26 publications
2
64
0
2
Order By: Relevance
“…We recommend consulting the quality indicators recommended by Schiele et al, which are included in Table . In a national cohort study using the MINAP registry, Bebb et al assessed the performance of hospitals according to the European Society of Cardiology Acute Cardiovascular Care Association quality indicators and 30‐day mortality for acute MI. Eleven quality indicators had a significant inverse association with 30‐day mortality (all P < .001), suggesting that quality indicators have the potential to improve patient healthcare and reduce varied mortality from acute MI (Figure ).…”
Section: Addressing the Challenges For The Treatment Of Patients Withmentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend consulting the quality indicators recommended by Schiele et al, which are included in Table . In a national cohort study using the MINAP registry, Bebb et al assessed the performance of hospitals according to the European Society of Cardiology Acute Cardiovascular Care Association quality indicators and 30‐day mortality for acute MI. Eleven quality indicators had a significant inverse association with 30‐day mortality (all P < .001), suggesting that quality indicators have the potential to improve patient healthcare and reduce varied mortality from acute MI (Figure ).…”
Section: Addressing the Challenges For The Treatment Of Patients Withmentioning
confidence: 99%
“…Association between the European Society of Cardiology Acute Cardiovascular Care Association quality indicators for acute myocardial infarction and crude 30‐day mortality. Adapted from Bebb et al The composite opportunity QI was divided into the following categories: zero, received no interventions out of those eligible for; low, received <40% of interventions eligible for; intermediate, received ≥40% to <80% of interventions eligible for; and high, received ≥80% of interventions eligible for. Abbreviations: ACEI; angiotensin‐converting enzyme inhibitor; ARB; angiotensin receptor blocker; BB, β‐blocker; CI, confidence interval; DAPT, dual antiplatelet therapy; EF, ejection fraction; HF, heart failure; LV, left ventricular; NSTEMI, non‐ST‐segment elevation myocardial infarction; PCI, percutaneous coronary intervention; QI, quality indicator; STEMI, ST‐segment elevation myocardial infarction…”
Section: Addressing the Challenges For The Treatment Of Patients Withmentioning
confidence: 99%
“…However, most registries do not have more recent data for data comparison. A recent publication with data from The Myocardial Ischaemia National Audit Project showed that, in our registry, we have similar rates of timely reperfusion in STEMI, particularly in primary PCI centres (a little longer in nonprimary PCI hospitals) and more NSTACS patients submitted to coronary angiography in the first 72 hours . Left ventricular function is more often assessed.…”
Section: Discussionmentioning
confidence: 52%
“…A recent publication with data from The Myocardial Ischaemia National Audit Project showed that, in our registry, we have similar rates of timely reperfusion in STEMI, particularly in primary PCI centres (a little longer in nonprimary PCI hospitals) and more NSTACS patients submitted to coronary angiography in the first 72 hours. 23 Left ventricular function is more often assessed. In our registry, the use of DAPT and statins is similar and a better rate of use of ACEI/ARB and beta blocker in patients with heart failure of left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Patients achieved the composite score whether the received all of the care interventions they were eligible for. The opportunity composite score originally consisted of 12 measures; however, MINAP data only allows assessment of nine measures combined using an equal weight method 9. QI inclusion and qualification is shown in the online supplementary table S2.…”
Section: Minapmentioning
confidence: 99%